PERTANGGUNGJAWABAN PIDANA PELAKU PENGANIAYAAN SECARA BERSAMA-SAMA TERHADAP ORANG DI MUKA UMUM YANG MENYEBABKAN LUKA (Studi Perkara Nomor 6/pid.B/2018/PN Sdn Tahun 2018) - andri akasi akasi; Erlina B; Anggalana Anggalana (Universitas Mitra Indonesia, 2021)
The use of violence by someone against another person is prohibited in the Criminal Law because the use of violence brings consequences in the form of injury or death. For this reason, the Criminal Code has been formulated and threatened with criminal acts in various ways and as a result of acts that use violence. The problem in this research is what are the factors that cause perpetrators of criminal acts of persecution together against people in public that cause injuries based on Case Number 6 / Pid.B / 2018 / PN Sdn Year 2018, how criminal liability of perpetrators of persecution together against people in public who cause injuries based on Case Number 6 / Pid.B / 2018 / PN Sdn Year 2018, how judges considerations in applying sanctions against perpetrators of persecution together against people in public who cause injuries based on Case Number 6 / Pid.B / 2018 / PN Sdn 2018. The research method uses a normative and empirical juridical approach. The type of data used is secondary data and primary data. Collecting data through library research and field research. Analysis of the data used is qualitative juridical.